Penerapan Arsitektur Panopticon Pada Lembaga Pemasyarakatan Perempuan Di Pekanbaru - Mita Fransisca Rumapea; Yohannes Firzal; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Panopticon is a large circular building in which along the circle edge there are rooms and there is a watchtower in the middle. Panopticon is an embodiment of a monitoring system that has an important role to accentuate the power discipline and this knowledge is very appropriate if applied to Correctional Institutions. Correctional Institutions with the application of Panopticon not available yet in Pekanbaru, especially the Women's Correctional Institution, since the women's correctional facilities in Pekanbaru are currently hitching at the Pekanbaru Class II Special Guidance Institution. The security system applied by the panopticon architecture at the Women's Penitentiary in Pekanbaru is expected to provide direct effects such as creating an order and safe atmosphere also can maximize the role of Correctional Institutions in providing guidance in the form of resociality and reintegration along with its supervision. The method used in the design is to apply the principle of power discipline which is the main influence in the application of panopticon. The concept used is Limited Freedom. This concept is based on the function of correctional institutions as a place for fostering prisoners whose freedom are taken away during the coaching period, with a very strict administrative system without forgeting the prisoners' rights. when they are released they do not repeat their criminal acts and get a deterrent effect while in a correctional institution.Keyword: Correctional Institution, Women's Correctional Institution, Panopticon Architecture